2020
DOI: 10.1155/2020/5686894
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Repeatability of Automated Superficial Retinal Vessel Density according to the Measurement Area Using OCT Angiography

Abstract: Purpose. To evaluate the difference in the repeatability of automated superficial retinal vessel density and foveal avascular zone (FAZ) metrics according to the measurement area of optical coherence tomography angiography (OCTA). Methods. A total of 127 normal eyes from 127 healthy subjects were included. Macular angiography images were acquired from all subjects using the Zeiss Cirrus 5000 with AngioPlex™ OCTA software. Scans of 3 × 3 mm and 6 × 6 mm were each performed twice in a randomly arranged sequence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In our study, we used 3 × 3-mm macular angiography scans, which appear to be more suitable than larger ones (6 × 6-mm scans) for quantitatively analyzing the macular microvascular metrics and the FAZ in terms of repeatability ( 36 ). We observed a statistically significant reduction in vascular density indices in both SCP and DCP in FD patients compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used 3 × 3-mm macular angiography scans, which appear to be more suitable than larger ones (6 × 6-mm scans) for quantitatively analyzing the macular microvascular metrics and the FAZ in terms of repeatability ( 36 ). We observed a statistically significant reduction in vascular density indices in both SCP and DCP in FD patients compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Given that 3 × 3-mm OCTA scans may be more useful in identifying subtle macular microvascular changes, it is possible that the 3 × 3-mm OCTA scan is the preferred method for detecting novel biomarkers in amnestic and nonamnestic MCI patients. 25…”
Section: Discussionmentioning
confidence: 99%
“…However, good repeatability and reproducibility of FAZ area measurements performed with the AngioPlex software were shown in both 6×6 mm and 3×3 mm scan areas previously. 26 Furthermore, a comparative study found that macular OCTA 6×6 mm scans detect glaucomatous changes better than 3x3 mm scans. 27 The FAZ area was suggested as a good indicator of macular capillary health and linked to ischemic ocular disease progression.…”
Section: Discussionmentioning
confidence: 99%